(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
Information from financial reports is the basis upon which users of financial information make various decisions accounting measurement based on historical cost is objective and reliable but not appropriate, as it reflects past events and does not provide future information, hence the global trend of replacing historical cost with fair value, since the information generated is relevant and reflects the unit’s true financial position. The research therefore sought to illustrate the impact of fair value adoption on the quality of financial reporting. The importance of research stems from the importance of quality financial reporting because of its significant influence on decision makers.Given the international trend to replace the historical cost basis with fair value accounting measurement, it was important to examine the ability of fair value financial reporting to provide users of financial reporting with financial information and indicators that are appropriate and useful for good economic decision-making and also to identify underlying causes Behind the trend of preparers of International Accounting Standards (IAS) and International Financial Reporting Standards (IFRS) to use fair value in accounting measurement. To test the validity of the research hypothesis, the impact of using fair value on the quality of financial reporting was measured by measuring the adequacy of financial reporting at Baghdad commercial bank . The researchers came to several conclusions, the main one being that there is an impact of using fair value on bank activities after its application. They recommended that efforts be made to apply fair value across a wider range of financial assets to include all their assets and liabilities properly according to the International Financial Reporting Standards (IFRS), as the impact may become clearer.